2013
DOI: 10.1007/s13659-013-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Manuka honey: an emerging natural food with medicinal use

Abstract: Abstract:The health value of honey is universally acknowledged from time immemorial. Manuka (Leptospermum scoparium) is a tree, indigenous to New Zealand and South East Australia, and from the myrtle family, Myrtaceae. The honey produced from its flowers is a uni-floral honey largely produced in New Zealand. It is becoming increasingly popular as a functional food, seen in the aisles of health stores as its displays superior nutritional and phytochemistry profile over other varieties of honey. Examining existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…Manuka honey contains a high amount of phenolic compounds [ 14 , 15 ], as well as other phenolic compounds that have been identified with a potent capacity to reduce free radicals, providing a relevant antioxidant capacity [ 56 , 57 ]. For its relevant bioactive properties, it has often been used in different studies as the “gold standard” [ 8 ] to test and evaluate the antioxidant capacity of different kinds of honey from different botanical and geographical origins. Manuka honey, in fact, exhibits the highest value in terms of phenolic content and antioxidant capacity, for example compared to acacia, wild carrot and Portobello honeys [ 58 , 59 ], obtained, respectively, from Germany, Algeria, Saudi Arabia and Scotland.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Manuka honey contains a high amount of phenolic compounds [ 14 , 15 ], as well as other phenolic compounds that have been identified with a potent capacity to reduce free radicals, providing a relevant antioxidant capacity [ 56 , 57 ]. For its relevant bioactive properties, it has often been used in different studies as the “gold standard” [ 8 ] to test and evaluate the antioxidant capacity of different kinds of honey from different botanical and geographical origins. Manuka honey, in fact, exhibits the highest value in terms of phenolic content and antioxidant capacity, for example compared to acacia, wild carrot and Portobello honeys [ 58 , 59 ], obtained, respectively, from Germany, Algeria, Saudi Arabia and Scotland.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…These anticancer properties can involve different processes: (1) the apoptosis of cancer cells through the depolarization of the mitochondrial membrane, (2) the inhibition of cyclooxygenase-2 by various constituents (like flavonoids), (3) the release of cytotoxic H 2 O 2 and (4) the scavenging of ROS and have been correlated with the phytochemical compounds [ 65 ]. Manuka honey has been shown to possess a potent anti-proliferative effect on murine melanoma (B16.F1), colorectal carcinoma (CT26) and human breast cancer (MCF-7) cell lines in a time- and dose-dependent manner [ 8 ]. The main mechanism by which it exerts such an anti-proliferative effect is through the activation of mitochondrial apoptotic pathways, involving the stimulation of the initiator, caspase-9, which determines the activation of the executioner, caspase-3 [ 65 ].…”
Section: Other Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manuka honey is a unifloral honey derived from the manuka tree, Leptospermum scoparium , belonging to the family Myrtaceae in New Zealand and the Eastern region of Australia [ 10 ]. It is a dark honey and has attracted a lot of attention, especially in regard to its antimicrobial agent, antioxidant efficacy, and potential role in wound healing [ 11 , 12 ]. Compared to other honey types, manuka honey contains the highest amount of phenolic and flavonoid compounds (pinobanksin, pinocembrin, and chrysin) that have been identified with potent ROS scavenging activity [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dark honey, Manuka Honey, has attracted attention for its biological properties, especially as an anti-viral effect. Several studies have been shown that there are many flavonoids and polyphenolic compounds in Manuka honey constituent [18][19][20][21] which suggested being accountable to its anti-microbial, anti-viral, and antioxidant effects [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%